Systematic synthesis of a 6-component organic-salt alloy of naftopidil, and pentanary, quaternary and ternary multicomponent crystals - Dandela, Rambabu; Tothadi, Srinu; Marelli, Udaya Kiran; Nangia, Ashwini (IUCrJ, 2018)
The single-crystal X-ray structure of a 6-component organic-salt alloy (hexanary) of naftopidil (1) (an active pharmaceutical ingredient) with benzoic acid (2) and four different hydroxy-substituted benzoic acids, i.e. salicylic acid (3), 2,3-dihydroxybenzoic acid (4), 2,4-dihydroxybenzoic acid (5) and 2,6-dihydroxybenzoic acid (6), is reported. The hexanary assembly originates from the observation that the binary salts of naftopidil with the above acids are isostructural. In addition to the 6-component solid, we also describe five 5-component, ten 4-component, and ten 3-component organic-salt alloys of naftopidil (1) with carboxylic acids (2)-(6). These alloys were obtained from different combinations of the acids with the drug. The synthetic design of the multicomponent organic alloys is based on the rationale of geometrical factors (shape and size) and chemical interactions (hydrogen bonds). The common supramolecular synthon in all these crystal structures was the cyclic N+ - H center dot center dot center dot O- and O-H center dot center dot center dot O hydrogen-bonded motif of R-2(2) (9) graph set between the 2-hydroxyammonium group of naftopidil and the carboxylate anion. This ionic synthon is strong and robust, directing the isostructural assembly of naftopidil with up to five different carboxylic acids in the crystal structure together with the lower-level multicomponent adducts. Solution crystallization by slow evaporation provided the multicomponent organic salts and alloys which were characterized by a combination of single-crystal X-ray diffraction, powder X-ray diffraction, NMR and differential scanning calorimetry techniques.

Selective targeting of integrin alpha v beta 8 by a highly active cyclic peptide - Reichart, Florian; Maltsev, Oleg V.; Kapp, Tobias G.; Raeder, Andreas F. B.; Weinmueller, Michael; Marelli, Udaya Kiran; Notni, Johannes; Wurzer, Alexander; Beck, Roswitha; Wester, Hans Juergen; Steiger, Katja; Di Maro, Salvatore; et al. (Journal of Medicinal Chemistry, 2019)
Integrins play important roles in physiological and pathophysiological processes. Among the RGD-recognizing integrin subtypes, the alpha v beta 8 receptor is emerging as an attractive target because of its involvement in various illnesses, such as autoimmune diseases, viral infections, and cancer. However, its functions have, so far, not been investigated in living subjects mainly because of the lack of a selective alpha v beta 8 ligand. Here, we report the design and potential medical applications of a cyclic octapeptide as the first highly selective small-molecule ligand for alpha v beta 8. Remarkably, this compound displays low nanomolar alpha v beta 8 binding affinity and a strong discriminating power of at least 2 orders of magnitude versus other RGD-recognizing integrins. Peptide functionalization with fluorescent or radioactive labels enables the selective imaging of alpha v beta 8-positive cells and tissues. This new probe will pave the way for detailed characterization of the distinct (patho)physiological role of this relatively unexplored integrin, providing a basis to fully exploit the potential of alpha v beta 8 as a target for molecular diagnostics and personalized therapy regimens.